CACA guidelines for holistic integrative management of central nervous system germ cell tumor - Chao Zhang; Xiang Huang; Yijin Gao; Yang Wang; Hongying Ye; Hong Chen; Junping Zhang; Linbo Cai; Chunde Li; Yuqi Zhang; Jingsheng Wang; Songtao Qi; et al. (Holistic Integrative Oncology)
Abstract Central nervous system germ cell tumors (CNS GCTs) are common malignancies of the central nervous system of children and adolescents. The management of CNS GCTs is complex because of varied tumor sites, clinical presentations, treatments and outcomes. Multidisciplinary integrated treatment involving radiotherapy, chemotherapy and surgery is the most commonly used approach for CNS GCTs worldwide and is essential for achieving favorable clinical outcomes. The Pediatric Oncology Committee of the Chinese Anti-Cancer Association (CACA) has formulated the guidelines for the management of CNS GCTs based on domestic and foreign clinical studies and experiences. The guidelines cover the diagnosis and treatment of primary CNS GCT in the pineal region, the sellar region, and the thalamus and basal ganglia region, recurrent, disseminated, and bifocal/multifocal CNS GCT, as well as traditional Chinese medicine. In these guidelines, different treatment regimens are proposed for secretory or non-secretory GCTs. The therapeutic concepts of primary treatment and second-look surgery are also introduced. The hope is to help standardize the diagnosis and treatment, and further improve the outcomes of CNS GCTs patients.